Glycemic patterns and factors associated with post-hemodialysis hyperglycemia among end-sStage-renal disease patients undergoing maintenance hemodialysis - Yusof Khan, Abdul Hanif Khan; Zainal Abidin, Muhammad 'Adil; Zakaria, Nor Fadhlina; Seong Ling, Christopher Tiam; Kamaruddin, Nor Azmi (ASEAN Federation of Endocrine Societies (AFES), 2020)
Introduction. Chronic and post-prandial hyperglycemia are independent risk factors for diabetic complications. Glycemic patterns among hemodialysis end-stage-renal-disease (ESRD) differ as glucose metabolism changes with declining kidney function with more pronounced glycemic fluctuations. The objectives of this study are to determine glycemic patterns on hemodialysis days, the magnitude of post-hemodialysis rebound hyperglycemia (PHH) and their associated factors.